Population Aging and Its Impact on Human Wellbeing in China - Wang, Meng-Yun; Sung, Hsing-Chou; Liu, Jie-Yi (Frontiers in Public Health, 2022)
Population aging is getting enlarged in the upcoming decades. Meanwhile, old-aged longevity and dependency are getting large due to improvement in life expectancy. In literature, it is claimed that old-aged dependency affects the wellbeing of society. Thus, the study intends to explore the impact of population aging on human wellbeing. The study adopts the Autoregressive Distributed Lag (ARDL) approach for empirical analysis by using time-series series data from 1990 to 2020. The study findings reveal that an increase in population aging reports a significant and decreasing impact on human wellbeing. However, an increase in health expenditure reports a significant and increasing impact on human wellbeing. Thus, China must pay attention to population aging to improve human health.